Revealing the potential of fraud in the financial management of village-owned enterprise - Aprina Nugrahesthy Sulistya Hapsari; Intiyas Utami; Yohanes Yakobus Werang Kean (Jurnal Akuntansi dan Auditing Indonesia, 2021)
This research is a qualitative-descriptive study conducted to identify fraud that occurs in the financial management of BUMDes (Village-Owned Enterprises). BUMDes is a business entity established through village capital inclusion which aims to manage existing assets, services, and businesses for village income contribution. In connection with this capital management, villages are required to be fully responsible for managing their capital in a transparent and accountable manner. The object of this research is BUMDEs (Village-Owned Enterprise) X in Wologai Tengah Village of Ende, Flores, where data collection was obtained through in-depth interviews with sources and documentation of documents that can support the results of this research. The results show that BUMDes X in Wologai Tengah Village of Ende, Flores is still vulnerable to the potential risk of fraud. This is because some parties still feel that their interests are more important than that of others. However, BUMDes X still promotes a culture of deliberation that involves the community in making decisions.